2022
DOI: 10.1038/s42004-022-00783-4
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution spectroscopy of buffer-gas-cooled phthalocyanine

Abstract: For over five decades, studies in the field of chemical physics and physical chemistry have primarily aimed to understand the quantum properties of molecules. However, high-resolution rovibronic spectroscopy has been limited to relatively small and simple systems because translationally and rotationally cold samples have not been prepared in sufficiently large quantities for large and complex systems. In this study, we present high-resolution rovibronic spectroscopy results for large gas-phase molecules, namel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Slow beam velocities in the laboratory frame and a wide applicable temperature range are important characteristics of buffer gas cooling. Currently, numerous spectroscopic studies using buffer gas cooling have been reported. …”
Section: Introductionmentioning
confidence: 99%
“…Slow beam velocities in the laboratory frame and a wide applicable temperature range are important characteristics of buffer gas cooling. Currently, numerous spectroscopic studies using buffer gas cooling have been reported. …”
Section: Introductionmentioning
confidence: 99%